Marsupiales (Didelphimorphia: Didelphidae) de Iquitos y sus alrededores (Loreto, Perú) - Díaz, M. Mónica (THERYA, 2014)
Introduction: Amazonia has a high diversity of marsupials, and while Emmons and Feer (1990) have cited 14 species for the area, 18 years later this number was increased to 28 by Gardner (2008a), a difference related to descriptions and revalidation of several species in recent years. Northeastern Peru is one of the areas with high biodiversity, a â€œhotspotâ€. The high diversity of small mammals can be explained by several factors: latitudinal gradient, size of the area, and lack of seasonal precipitations, among others. In this contribution 19 species are cited for the region of Iquitos, 14 collected through field trips and five recorded from the literature. These results confirm the presence of a species that was not known for the country (Marmosops neblina), and two species (Marmosa regina and Marmosops bishopi) with new records for the area. The results show that the study area is one of the most diverse in South America with respect to marsupials. Material and methods: The specimens were collected between December 2002 and December 2005, at 41 collecting sites along the Iquitos-Nauta Highway. The study was carried out in undisturbed primary and secondary forests, and other rural areas. In total, 18,081 Sherman trap-nights, 19,271 Tomahawk trap-nights, and 591 pitfall trap-nights were recorded. External and cranial morphometric data, body mass, sex, and reproductive condition were recorded for all specimens. A key to species is provided including the confirmed and probable species of the area. Species accumulation curves were calculated and plotted using EstimateS 8.2.0. Results: Three hundred and seventy three records were obtained belonging to 14 out of 27 species cited for the area; eight species were collected outside the Iquitos area. Most specimens were collected in primary and secondary forests (123 and 199 specimens respectively), only 49 were captured in other areas. Pitfall traps were the most successful (1.69% capture success), followed by Tomahawk traps (1.29%), and Sherman traps (0.55%). Arboreal traps were more successful than the ground traps, with 4.18% and 0.89% capture success respectively. The species accumulation curve did not reach stability and the estimates calculated are greater than the recorded species. Discussion: During three years of sampling, 14 species were collected, a number that rises to 19 when literature citations for the specific area of Iquitos are considered (and increases to 27 if the area is extended to a 200 km radius around Iquitos). Some species were very abundant (P. opossum, M. nudicaudatus, D. marsupialis, and M. regina), while others were documented by only 1 or 2 records (G. venusta, M. adusta, and P. olrogi). It is evident that the Peruvian Amazon is one of the areas with the highest diversity of marsupials, but further surveys and studies are necessary in order to determine with greater precision the distribution of many species, and to acquire a better understanding of their natural history. More extensive studies of the fauna of the region are required to obtain informational bases that will provide a strong management policy, in order to preserve the species in such a highly fragmented region. Key words: diversity, marsupials, natural history, Peruvian Amazon.